2015
DOI: 10.4236/jbm.2015.37004
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Isolates and Plasmid Profile of Extended Spectrum Beta-Lactamases Producers Causing Urinary Tract Infection among Pregnant Women in Uyo, Nigeria

Abstract: Background: Extended spectrum beta-lactamases (ESBLs) are enzymes that compromise the efficacy of all beta-lactams and are spread by plasmids. They are of public health importance the world over; however, in Nigeria in general and Uyo in particular, tests for their detection are not routinely done in hospital laboratories despite increase in treatment failures observed for common clinical conditions like urinary tract infection. Objective: To isolate ESBLs producing uropathogens and the plasmid underlying thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 12 publications
1
11
1
Order By: Relevance
“…Many reports showed that UTI is common in patients with different symptoms [14]. However, our concern in this study is to focus on pregnant women at different age group were they believed to have highest infection rate [2,14]. Due to the fact that untreated UTI in pregnancy can increases the risks of morbidity, and mortality to pregnant women and infant [17], keeping in mind that estimated 40 percent of women reported to have UTI some time in their lives [15], and by nature women are more susceptible to UTI because accessibility of organism to invade urethra and bladder easier than men [18].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many reports showed that UTI is common in patients with different symptoms [14]. However, our concern in this study is to focus on pregnant women at different age group were they believed to have highest infection rate [2,14]. Due to the fact that untreated UTI in pregnancy can increases the risks of morbidity, and mortality to pregnant women and infant [17], keeping in mind that estimated 40 percent of women reported to have UTI some time in their lives [15], and by nature women are more susceptible to UTI because accessibility of organism to invade urethra and bladder easier than men [18].…”
Section: Introductionmentioning
confidence: 99%
“…This is partially due to the short and wider female urethra and its proximity to anus. Bacteria from the rectum can easily travel up the urethra and cause infections [2,19,20]. Other factors reported to increase rate of infection are pregnancy and sexual intercourse [19], due to vaginal trauma which enhance access of bacteria to urethral into bladder [2,17,19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations